2021
DOI: 10.1039/d0bm02058c
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a nanofiber network within 3D printed scaffolds for vascularized bone regeneration

Abstract: Three-dimensional (3D) printed scaffolds provide promising perspective in bone tissue engineering. 3D printed scaffolds with micro- and nano-fibrous structure that facilitates the cell adhesion and migration, and combined vascularization and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…Some pioneering studies have been attempted to address this issue, such as the use of thermally induced phase separation (TIPS) technique to fabricate nanofiber structures in 3D printed scaffolds to promote cell ingrowth and neo‐tissue formation. [ 5 ] Although the porous structures, as an essential factor in scaffolds, could offer suitable microenvironment for the adhesion, proliferation, and differentiation of cells as well as biomineralization, however, it alone is insufficient which lacks biological cues for guiding angiogenesis and osteogenesis. [ 6 ] Recently, it has been reported that microchannels scaffolds with the tubular structures could promote the invasion of blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Some pioneering studies have been attempted to address this issue, such as the use of thermally induced phase separation (TIPS) technique to fabricate nanofiber structures in 3D printed scaffolds to promote cell ingrowth and neo‐tissue formation. [ 5 ] Although the porous structures, as an essential factor in scaffolds, could offer suitable microenvironment for the adhesion, proliferation, and differentiation of cells as well as biomineralization, however, it alone is insufficient which lacks biological cues for guiding angiogenesis and osteogenesis. [ 6 ] Recently, it has been reported that microchannels scaffolds with the tubular structures could promote the invasion of blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…The usual techniques for preparing modified polyesters for artificial bone-substitute materials involve 3D printing [ 51 , 61 , 65 , 66 , 72 , 74 , 75 , 76 ], thermally induced phase separation (TIPS) [ 32 ], salt leaching [ 32 , 69 , 79 ], solvent casting [ 33 , 35 , 77 , 79 ], electrospinning [ 60 , 64 , 70 ], copolymerization [ 31 ], and polycondensation [ 73 ].…”
Section: Orthopedic Applicationsmentioning
confidence: 99%
“…Besides electrospinning, other techniques, such as TIPS and DIPS, were also used with freeze-drying as hybrid fabrication technologies for TE scaffolds. Geng et al [ 107 ] developed a 3D-printed biodegradable poly (glycerol-co-sebacic acid-co- l -lactic acid-co-polyethylene glycol) (PGSLP)-based scaffold that was internally filled with gelatin nanofibers. They fabricated the nanofibrous structured gelatin/PGSLP (NGP) scaffold employing a thermally induced phase separation (TIPS) technique, and then the macroporous structured gelatin/PGSLP (MGP) scaffold was prepared by directly freeze-drying.…”
Section: Combination Of Solution-based Techniquesmentioning
confidence: 99%